Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1089/adt.2020.987
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Glimepiride-Loaded Gelatin-Coated Mesoporous Hollow Silica Nanoparticle Formulation and Evaluation of Its Hypoglycemic Effect on Type-2 Diabetes Model Rats

Abstract: In this study, we prepared gelatin-coated mesoporous hollow silica nanospheres (GSN) as a drug carrier to improve the water solubility and regulate the release rate of glimepiride (GLM). GLM was loaded into GSN by an absorption method, and drugloaded samples (GLM-GSN) were characterized by differential scanning calorimeter (DSC) and X-ray diffraction (XRD). Cellular uptake and in vivo intestinal uptake experiments were performed in rats. In addition, the studies of in-vitro drug dissolution, pharmacokinetics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This functional diversity allows it to be modified by using nanoparticles and biomolecules. In addition, gelatin is an extracellular matrix protein which allows it to be applied in wound dressings, drug delivery, and gene transfection [ 252 , 253 , 254 ]. It presents desirable features, such as natural origin, low-cost, low-toxicity, biodegradability, and non-immunogenicity, although it shows poor stability in aqueous solutions [ 255 ].…”
Section: Functionalization Of Msns With Biopolymersmentioning
confidence: 99%
“…This functional diversity allows it to be modified by using nanoparticles and biomolecules. In addition, gelatin is an extracellular matrix protein which allows it to be applied in wound dressings, drug delivery, and gene transfection [ 252 , 253 , 254 ]. It presents desirable features, such as natural origin, low-cost, low-toxicity, biodegradability, and non-immunogenicity, although it shows poor stability in aqueous solutions [ 255 ].…”
Section: Functionalization Of Msns With Biopolymersmentioning
confidence: 99%
“…Glimepiride-GSNs showed 40% drug release at 1 h and more than 90% during 24 h. In addition, this study revealed that the T max , mean residence time (MRT), and 24-h area under the curve (AUC 0-24h ) values in glimepiride-GSNs were significantly higher than the commercially available product counterparts. Moreover, the bioavailability of glimepiride was enhanced after incorporation into the GSNs and also lead to higher cellular and intestinal mucosal uptake (Yu et al, 2020).…”
Section: Particle Sizementioning
confidence: 99%
“…These formulations were able to prolong the encapsulated drug release up to 60 h and the treatment of cell cultures by obtained formulations showed good viability of MRC-5 fibroblast cells and suppression of HeLa cells [238]. The authors of [239] designed gelatin-coated mesoporous hollow silica nanospheres and used them for glimepiride encapsulation. Formulations were characterized by high drug loading (40%) and more than a 2-fold higher duration of hypoglycemic effect in comparison with commercially available formulations, which allows researchers to recommend them as perspective candidates for the treatment of type 2 diabetes.…”
Section: Mesoporous Silica Nanoparticles Modified By Natural Polymersmentioning
confidence: 99%